2017
DOI: 10.21608/zvjz.2017.7867
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of a Commercial Live Attenuated aroA mutant Vaccine Against Avian Pathogenic Escherichia coli Challenge in Broilers

Abstract: Avian colibacillosis is an infectious disease of domestic poultry with economic importance. Among the tools available for the control avian pathogenic E. coli (APEC), vaccines have received the most attention. In this research, comparative bacteriological examination between candidates of live aroA mutant E. coli vaccine and two virulent APEC strains (O78 and O125) was carried. Innate immunity (leukogram & Phagocytosis) as well specific cellular (CD4 & CD8) and humoral (agglutinins) immune response of vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…Additionally, clinical and lesion scores were higher compared to the negative control groups. The performance parameters and the detection of APEC O 125 challenge strain in both vaccinated challenged and challenge control groups were almost the same [ 28 ]. These results indicate the failure of the attenuated E. coli derivatives (deleted gene mutants) to protect against heterologous challenge [ 24 , 29 ] confirming Kariyawasam and co-workers’ finding that the protection conferred by mutant E. coli vaccine is serogroup specific [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, clinical and lesion scores were higher compared to the negative control groups. The performance parameters and the detection of APEC O 125 challenge strain in both vaccinated challenged and challenge control groups were almost the same [ 28 ]. These results indicate the failure of the attenuated E. coli derivatives (deleted gene mutants) to protect against heterologous challenge [ 24 , 29 ] confirming Kariyawasam and co-workers’ finding that the protection conferred by mutant E. coli vaccine is serogroup specific [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike young chickens in which immunity largely depends on activity of the innate immune system as well as on maternal antibodies, in adult birds the adaptive immune system is fully developed and functional T and B cell responses can be expected ( 24 ). Although, the development and role of immune cells regarding an APEC infection in chicken is highlighted ( 25 ) little has been published explaining the dynamics of the immune system of E. coli infected chickens using flow cytometry on samples of circulating cells such as monocytes/macrophages, CD4 + or CD8 + cells ( 17 , 26 , 27 ). Recently, investigations on cytokine production of T cells after ex vivo re-stimulation revealed significantly elevated levels of APEC-specific IFN-γ-producing CD8α, CD4, TCR-γδ cells in lung, spleen and blood mononuclear cells of naïve specific pathogen-free (SPF) chickens ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a field trial, the Poulvac vaccine did not affect the weight gain in broiler chickens [54]. In experimental conditions, several studies have suggested its efficacy against homologous challenge in reducing colibacillosis-associated pathological lesions [54][55][56][57][58]. Oral vaccination of birds at day 5 of age reduced morbidity [59] but drinking water application was found to be ineffective in inducing protection [56].…”
Section: Live and Live Attenuated Vaccinesmentioning
confidence: 99%
“…Oral vaccination of birds at day 5 of age reduced morbidity [59] but drinking water application was found to be ineffective in inducing protection [56]. The findings regarding heterologous protection were not consistent among studies with some showing effectiveness against certain strains [54,60], but not others [56,57,60]. The efficacy of the vaccine against homologous challenge was enhanced by supplementation of probiotics Enterococcus faecalis [58] and pre-treatment with Lincospectin improved the vaccine's response [61].…”
Section: Live and Live Attenuated Vaccinesmentioning
confidence: 99%